Comparative Analysis of The Digitization of the European Union and Serbia Based on the MEREC and MARCOS Methods - LUKIC, Radojko (Informatica economica, 2024)
In recent times, digitization is increasingly becoming a critical factor in business success. Given this, knowing the level of digitization is a key assumption for improvement in the future. Bearing that in mind, this study comparatively analyzes the level of digitization of the member states of the European Union (EU) and Serbia using the MEREC and MARCOS methods. The results indicate which member states of the European Union need to speed up the digitization process to achieve the optimal level of success in realizing the target business. A higher level of digitization means better business success. In the European Union, the highest level of digitization is in the Netherlands. Next: Finland, Sweden, Denmark, Spain and so on. The leading countries of the European Union are positioned: Germany is in eighteenth place, France is in fourteenth place and Italy is in twentieth place. In the European Union, in terms of digitization, Romania took the worst position. Serbia (twenty-eighth place) is therefore in a very bad position among the member states of the European Union and in the surrounding area (Croatia is in thirteenth place, and Slovenia is in sixteenth place). In Serbia, to achieve the desired business success, it is necessary to significantly increase the level of digitization.